European integration as a peace project. (February 2017) - Birchfield, Vicki L; Krige, John; Young, Alasdair R
Using the Norwegian Nobel Committee's justification for awarding the 2012 Nobel Peace Prize to the European Union (EU) as a foil, this article examines the EU through the prism of being a peace project. It contends that European integration reflects a Wilsonian liberalism approach to building peace, which emphasizes free trade and democracy, but with a distinctly European twist; an additional emphasis on functional integration and institutionalization, as well as a regional focus. It also identifies three themes that run through the contributions to the special section. First, there has been a strong dialectic between the internal and external dimensions of security in the European integration project from the outset. In some ways, these have been reinforcing, but in others, they have been contradictory. Second, the European peace project has passed though successive, if often overlapping, chronological phases. These phases have been defined by different security challenges that called for different policy approaches. Russian aggression and jihadi terrorism characterize the most recent phase. The third theme is that, despite the changes in terms of threats and policies, there has been a remarkable consistency in two reinforcing respects: the persistent tension among the member states about closer integration with respect to the external security, and the tendency of the EU to emphasize institution building and to neglect strategy. The article concludes with a dialogic introduction to the individual contributions.